2007
DOI: 10.1074/jbc.m610631200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of AMPK and mTOR in Nutrient Sensing in Pancreatic β-Cells

Abstract: The AMP-activated protein kinase (AMPK) is a central regulator of the energy status of the cell, based on its unique ability to respond directly to fluctuations in the ratio of AMP:ATP. Because glucose and amino acids stimulate insulin release from pancreatic ␤-cells by the regulation of metabolic intermediates, AMPK represents an attractive candidate for control of ␤-cell function. Here, we show that inhibition of AMPK in ␤-cells by high glucose inversely correlates with activation of the mammalian Target of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
138
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 55 publications
10
138
1
3
Order By: Relevance
“…In the present study, we found that short-term treatment with the AMPK activator AICAR stimulated insulin secretion, an effect that was independent of glucose concentration and was mediated by inhibition of K ATP channel activity. Stimulation of insulin secretion in response to AMPK activation by AICAR at physiological glucose concentrations [16][17][18]48] is in agreement with our present findings.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found that short-term treatment with the AMPK activator AICAR stimulated insulin secretion, an effect that was independent of glucose concentration and was mediated by inhibition of K ATP channel activity. Stimulation of insulin secretion in response to AMPK activation by AICAR at physiological glucose concentrations [16][17][18]48] is in agreement with our present findings.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the effects of metformin on insulin secretion are more controversial; Marchetti and colleagues (Lupi et al, 1997) have provided evidence that insulin secretion is stimulated by metformin in islets from type 2 diabetics, perhaps reflecting respiratory chain inhibition and suppressed reactive oxygen species (ROS) production. By contrast, our own findings using islets from both rodent and human (Leclerc et al, 2004b) It should also be mentioned that two other groups (Wang et al, 2005;Gleason et al, 2007) have provided evidence which argues against a role for AMPK in the control of insulin secretion. In the first of these studies, AICAR was shown to stimulate secretion from isolated islets; it must be stressed, however, that this riboside may have complex effects, including, after triple phosphorylation to generate an ATP analogue (ZTP), closure of ATP-sensitive K + channels, likely to activate insulin release.…”
Section: Role Of Ampk Activation In Insulin-target Tissuescontrasting
confidence: 67%
“…In the first of these studies, AICAR was shown to stimulate secretion from isolated islets; it must be stressed, however, that this riboside may have complex effects, including, after triple phosphorylation to generate an ATP analogue (ZTP), closure of ATP-sensitive K + channels, likely to activate insulin release. On the other hand, Gleason et al (Gleason et al, 2007), using the strongly glucose-responsive INS-1(832/13) cell line, as well as MIN6 cells, demonstrated that expression of an inactivated form of AMPK (2K 45 R) exerted no effect on basal or glucose-stimulated insulin secretion, arguing against a controlling role for AMPK.…”
Section: Role Of Ampk Activation In Insulin-target Tissuesmentioning
confidence: 99%
“…AICAR has been postulated to mediate its anti-growth effects primarily through mTOR inhibition (14,28). Thus, the demonstration that its effects were mediated primarily through inhibition of lipogenesis was quite unexpected.…”
Section: Discussionmentioning
confidence: 99%